Phytodiversity Analysis of Boudh District (Odisha) of Eastern India - Sahu, C. R. (Indian Forester, 2016)
The present paper deals with analysis of phytodiversity in Boudh district of Odisha, Eastern India. The district lies between 20° 22' to 20° 50' N Latitude and 83° 34' to 84° 49' E Longitude and has a forest area of 3,098 km2 i.e. 40.51%. A total of 575 species belonging to 129 families are recorded across the study sites, of which 223 are herbs, 152 are trees, 101 are shrubs and 99 are other life forms. Among these Fabaceae (48), Poaceae (31), Asteraceae (24), Euphorbiaceae (23), Rubiaceae and Malvaceae (16 each) are the most abundant families. The Dicots and Monocots were represented by 99 and 19 families respectively. The ratio of family to genus was 1: 3.3, family to species was 1: 4.35 and a genus to species was 1:1.35. It is concluded that present study will promote forest conservation, management, plant diversity research and as a reference of plant species distribution and availability.